OSING MIND: Pendampingan Psikososial Berbasis Budaya Lokal Osing bagi Lansia sebagai Upaya Mengurangi Kesepian di Panti Jompo Sahabat Lansia - Dian Roshanti; Akhmad Yanuar Fahmi Pamungkas; Roudlotun Nurul Laili; Muhammad Nashir; Johan Widjaya (Lembaga Pengembangan Kinerja Dosen, 2026)
Loneliness among older adults is a psychosocial issue that requires attention because it can affect mental health, quality of life, and social engagement, especially among those living in nursing homes. This community service activity aimed to describe the implementation of the OSING-MIND program as a psychosocial assistance model based on local Osing culture for older adults at Sahabat Lansia Nursing Home, Blambangan Village, Muncar District, Banyuwangi Regency. The activity used a community-based psychosocial assistance approach with a pre- and post-activity evaluation design involving 40 older adults. The program was conducted in six sessions: Ngerti Rasa, Sadar Napas, Kelingan Sing Apik, Nata Pikir, Guyub Rukun, and Urip Ana Maknane. Each session integrated simple mindfulness practices, reminiscence, positive affirmations, social interaction, life-meaning reflection, and local Osing cultural values. Evaluation was conducted through loneliness score measurement, participant engagement observation, and feedback from participants and nursing home staff. Results showed a decrease in the mean loneliness score from 7.05 to 3.40. No participants remained in the high loneliness category after the activity. These findings suggest OSING-MIND is contextual, humanistic, and applicable for elder care.